PENAMBAHAN RAGI DAN EKSTRAK BIJI JAGUNG TERHADAP PERTUMBUHAN TUNAS MANGGIS SECARA IN VITRO In Vitro Addition of Yeast and Corn Seed Ekstract on the Growth of Shoots Mangosteen (Garcinia mangostana L.) - Damiska, Septi; Wulandari, Reine Suci; Darwati, Herlina (Universitas Tanjungpura, 2015)
ABSTRACT Mangosteen is one of the types of plants that have a high economic value and become a commudity export market internationally. This is because the mangosteen has many beneficial uses. Mangosteen is one of tropical forest trees that have the correct length of the cycle and have a less good rooting systems making it difficult to grow naturally. So, the mangosteen seeds procurement needs to be done quickly and in an excellent quality to support the productivity of the mangosteen. One of the ways that can be done is with the technique of tissue culture. The research aimed to get the concentration of yeast, corn seed extract as well as the combination of yeast and corn seed extract which is optimum for budding multiplication mangosteen and the mangosteen shoots long added. The research was carried out using the basic method of complate random design arranged in a factorial with two factors, namely the yeast with 5 degrees of treatment (control, R1=7%, R2=8%, R3=9%, R4=10%) and corn seed extract with 5 treatment levels (control, J1=7%, J2=8%, J3=9%, J4=10%)Â so there are 25 treatment with 3 replicates and earned 75 units of the experiment. The results showed the best yeast concentration in the yeast is added the number of shoots with a concentration of 9% while the increase in the concentration of the best corn number of shoots was with a concentration of 8%. To increase the length of the shoots of the mangosteen, the best yeast concentration is 8%, while the best corn seed extract is concentration on 0%. The best combination between the yeast and corn seed extract in the amount of the increase of the mangosteen is R3J2 and shoots to high value added mangosteen shoots, a combination of yeast and corn seed extract is best R2J0. Keyword : Garcinia mangostana, yeast, corn seed ekstract